Pengaruh Kualitas Produk dan Harga terhadap Minat Beli Ulang Produk Blush On Wardah di Kota Cimahi - Zahra, Elma Annisa; Lestari, Dian (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study tries to investigate the influence between product quality and price on the desire to repurchase Wardah blush products in Cimahi city. This study applied a questionnaire in its research technique and involved 90 people who had used Wardah blush products in Cimahi. Purposive sampling is a nonprobability sampling approach. Validity and reliability tests, as well as traditional assumption tests and multiple regression, were used in the analysis. Each of the three research hypotheses proposed was supported by empirical evidence. As an outcome of increasing quality of the assessed object's quality and assisting the assessed parties in their business growth, this study is meant to be useful to future comparable studies and the assessed parties.